Students’ Perceptions of Student Support Services at a Nursing Campus - Ndlela, Nokuthula Tholumusa; Brysiewicz, Petra (Africa Journal of Nursing and Midwifery, 2018)
The main purpose of this study was to describe students’ perceptions of student support services at a selected nursing campus in the eThekwini District of KwaZulu-Natal, South Africa. The content analysis of Elo and Kyngäs guided the research process. Non-probability purposive sampling was used to recruit fourth-year nursing students undertaking the diploma in nursing (general psychiatry, community) and midwifery (R425), and eight students were individually interviewed. The students’ perceptions of student support services revealed four categories, namely diversity of student support, relevance of feedback, peer mentoring, and applicability of non-academic support. The researcher recommends that a broader study on student support services at the campuses of the KwaZulu-Natal College of Nursing be undertaken. Standardisation of student support services is needed as well as making the services known to students, possibly in the form of a booklet or online information. Another recommendation is the improvement of library services in the form of better access and equity related to information technology and internet usage, the extension of library hours, and the hiring of an assistant librarian. Lastly, the development and formalisation of a peer mentoring policy involving the clinical department are recommended.